HPTLC, IR fingerprinting, and chemical composition analysis of commercial bitter orange (Citrus aurantium L.) hydrosols - Mohammad Ali Jahromi; Fatemeh Sahrapour; Amirhossein Sakhteman; Marjan Faghih; Hamed Etemadfard; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2024)
Citrus aurantium L. hydrosol extracted by steam distillation from its flowers is a highly consumed herbal product in the Iranian traditional market, widely used as a food flavor and therapeutic food and drinks. This study investigated ten commercial hydrosol samples of C. aurantium flowers produced by conventional extraction methods and industrial processes, as well as a laboratory-prepared control sample. A liquid-liquid extraction method and sonication were used to extract essential oils from commercial hydrosols. Samples were then subjected to GC/MS analysis. ATR-IR spectroscopy was another efficient tool used to analyze hydrosol samples. All HPTLC chromatograms exhibited a close resemblance between samples and controls. The cluster analysis was used to compare the results of GC/MS and IR screening. In the HCA dendrograms derived from the GC/MS data, most of the oil sample profiles were found to be very similar to those of the control. Linalool was the most abundant compound in eight samples and the control. α-Terpineol in all hydrosol samples and geraniol in five samples and control were other marker compounds. Ethyl disulfide, dillapiol, and hotrienol were detected in two samples that have not been reported in previous studies and might have resulted from the addition of other herbal hydrosols. Microbial content and pH values were within permissible limits in all samples, making them safe for oral consumption.